Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan Fiskus, Dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Pp 23 Tahun 2018 Tentang Wajib Pajak Yang Memiliki Peredaran Bruto Tertentu Dengan Persepsi Keadilan Wajib Pajak Sebagai Variabel Pemodera - Putri, Trisandi Eka (JRAK: Journal of Accounting Research and Computerized Accounting, 2020)
This study aims to determine the effect of taxpayers awareness, tax service quality and tax socialization on PP 23 Year 2018 tax compliance with perceptions of tax fairness as a moderating variable on KPP Pratama Subang Tax Office. This study uses descriptive quantitative method using primary data. Data collection techniques are questionnaires. The population in this study are taxpayers who have businesses/SMEs in Subang Regency, and samples in this study are SMEs taxpayers registered in KPP Pratama as many as 155 respondents. Hypothesis testing using multiple regression analysis and moderated regression analysis (MRA). The results of this study indicate that taxpayers awareness has a positive effect on taxpayer compliance, tax service quality has a positive effect on taxpayer compliance, tax socialization has a positive effect on taxpayer compliance, in addition simultaneous awareness of taxpayer, quality of tax services, and influential tax socialization positive for taxpayer compliance. However, with the inclusion of moderating variables namely the perception of tax fairness does not strengthen or weaken the awareness of taxpayers on taxpayer compliance, perceptions of tax justice do not strengthen or weaken the quality of tax services and perceptions of tax fairness do not strengthen or weaken taxation socialization on tax compliance.